Konten Video Matematika Youtube untuk Optimalisasi Blended Learning dengan Strategi Asesmen Berbasis Aplikasi Moodle - Wachid Nugroho (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2022)
Online and direct learning (blended learning) requires support for optimizing student competency achievements as well as alternative choices of assessment model that are objective, practical, and effective in measuring student learning outcomes in a valid way. This best practice writing uses a qualitative descriptive approach with the aim of, firstly, to describe the use of math learning video content on youtube social media accounts to support the optimization of student competency achievements. Second, describe the online assessment model in mathematics subjects based on the moodle application. Third, describe the ease of application of learning and assessment in terms of practicality for teacher and accessibility for students. The research data collection technique uses documentation and observations of the learning and assessment system that has been used so far as well as and interviews with vice principal for curriculum, teachers, and students. The results of the study indicate that the use of youtube content in the form of math learning videos can support the optimization of student competency achievements. While the online mathematical assessment model based on the moodle application with the multiple-choice model could display random questions well, namely random questions from the question bank, random number of questions, and random answer options. Making video content in an easy and practical way using the powerpoint and active presenter application then uploading it to youtube social media account. While the online assessment model is also easy and practical to use in all subjects with the help of the examview application and can be apllied to daily assessments, midterm assessments, end-of-semester assessment, and school exams.